2011
DOI: 10.2533/chimia.2011.704
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Mechanisms of Interfacial Photoinduced Electron Transfer Processes of Third Generation Photovoltaics and Photocatalysis

Abstract: Photoinduced electron transfer (PET) across molecular/bulk interfaces has gained attention only recently and is still poorly understood. These interfaces offer an excellent case study, pertinent to a variety of photovoltaic systems, photo-and electrochemistry, molecular electronics, analytical detection, photography, and quantum confinement devices. They play in particular a key role in the emerging fields of third-generation photovoltaic energy converters and artificial photosynthetic systems aimed at the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In Fig. 9(b), the computed (J ET eff ) 2 for electron transfer from the initially delocalized state to the LUMO + 2 PDI is compared to the experimentally determined k ET . Although (J ET eff ) 2 reects the same trend as the experimental k ET , it overestimates the difference in k ET within 2mm, 2mp, and 2pp.…”
Section: Electron and Hole Transfer Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 9(b), the computed (J ET eff ) 2 for electron transfer from the initially delocalized state to the LUMO + 2 PDI is compared to the experimentally determined k ET . Although (J ET eff ) 2 reects the same trend as the experimental k ET , it overestimates the difference in k ET within 2mm, 2mp, and 2pp.…”
Section: Electron and Hole Transfer Parametersmentioning
confidence: 99%
“…Charge transfer in organic molecules is a process that is of fundamental and practical importance in several areas of science and technology. Important technological innovations, such as organic solar cells, 1,2 water splitting devices, 3 or single molecule electronics, [4][5][6][7][8][9] heavily rely on the control of intramolecular charge transfer reactions. A detailed understanding of these reactions along complex molecules is therefore of prime importance.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems are modeled as donor-acceptor heterojunctions. Depending at the energy levels of the HOMO and LUMO of the two materials, the electrons and holes become separated; electrons fall into lower energy states and holes rise to higher energies [34,35]. Such charge separation decreases the radiative recombination.…”
Section: Electronic Interaction Verificationmentioning
confidence: 99%
“…For example, it was found that OH˙ is generated during the photolysis of ozone. Identifying the processes of the formation of ROS may help utilize ROS by avoiding its ill effects ( Bauer et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%